The Biological Foundations of Sarcopenia: Established and Promising Markers - Casati, Martina; Costa, Andrea Saul; Capitanio, Daniele; Ponzoni, Luisa; Ferri, Evelyn; Agostini, Simone; Lori, Elisa (Frontiers in Medicine, 2019)
Sarcopenia, the progressive loss of muscle mass and strength, is one of the major health issues in older adults, given its high prevalence accompanied by huge clinical and socioeconomic implications. Age-related changes in skeletal muscle can be attributed to mechanisms both directly and indirectly related to muscle homeostasis. Indeed, a wide spectrum of age-related modifications in the organism was shown to play a key role in the pathogenesis of sarcopenia. Not surprisingly, sarcopenia has sometimes been indicated as a syndrome stemming from the aging process, and not as univocal standalone disease. Due to the multidimensionality of sarcopenia, a single biomarker approach is not enough to explain the biology of this condition. The aim of this review is to suggest innovative and promising sarcopenia markers investigating the link between skeletal muscle and brain. Indeed, as a neurological origin of sarcopenia has been hypothesized, a new perspective on sarcopenia biomarkers may focus on the dysfunction of the neuromuscular junctions (NMJs). The core SNARE synaptosomal-associated protein of 25 kDa (SNAP25) accumulates in the plasma membrane of nerve terminals at NMJs and regulates exocytosis at peripheral and central synapses. Interestingly, mice studies have shown that SNAP25 affects the neuromuscular function. SNARE complex and, in particular, SNAP25 may represent a promising pathway to explore the molecular and cellular mechanisms regulating muscular homeostasis and concur at profiling the sarcopenia biological background.